PSYCHOMETRIC VALIDATION OF THE BAHASA MALAYSIA VERSION OF THE ORGANISATIONAL AND OPERATIONAL POLICE STRESS QUESTIONNAIRES - Masilamani, Retneswari; Bulgiba, Awang; Chinna, Karuthan (Malaysian Journal of Public Health Medicine, 2025)
This article aims to examine the reliability and validity of the Organisational (PSQ-org) and Operational (PSQ-op) Police Stress Questionnaires. The study subjects were police officers of all ranks under 2 police headquarters from 2 states and 1 State Police Contingent. Data were analysed using Cronbach’s Alpha test of internal consistency, exploratory factor analysis, and confirmatory factor analysis for validity. A cross-sectional study was conducted using a translated Bahasa Malaysia version of the 2 scales: Organisational and Operational Police Stress Questionnaires, on 431 participants. One randomly selected subsample of 130 was used for Exploratory factor analysis with the other 301 utilised for Confirmatory factor analysis. The internal consistency test for the 20-item Organisational and Operational Police Stress Questionnaires using Cronbach’s Alpha coefficient was 0.96 for both. Exploratory factor analysis revealed a single factor for each with an average variance extracted being 55% and 62% for Organisational and Operational Police Stress Questionnaires respectively. The modified confirmatory factor analysis model for both scales, through model refinement, generated satisfactory goodness of fit statistics for all the criteria, namely chi-square/degrees of freedom ( df), comparative fit index (CFI), Tucker Lewis Index (TLI), and Root Mean Square Error of Approximation (RMSEA). All items on both scales had factor loading values exceeding 0.60, except one item in PSQ-op, which remained acceptable. The reliability and validity test confirmed that the Organisational and Operational Police Stress Questionnaires are reliable and valid for assessing organisational and operational police stress among the Malaysian police force.